2017
DOI: 10.5897/ajar2017.12279
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between potassium (K) and calcium (Ca) on the severity of Yellow Sigatoka in banana plants

Abstract: The main control measure of Yellow Sigatoka (Pseudocercospora musae) in banana plants (Musa spp.) has been the planting of resistant varieties, and fungicide application. However, the use of adequately nourished plants is also emphasized as a complementary control method. This study evaluated the influence of interaction between potassium (K) and calcium (Ca) in nutrient solution on the severity of Yellow Sigatoka in banana. Evaluation included severity of disease, chlorophyll a and b contents, nutrient conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
1
0
4
Order By: Relevance
“…Isto demostra que a grade amostral adotada no presente trabalho (30 x 30m) foi suficiente para expressar a variabilidade espacial das variáveis, com alcance representativo e capaz de captar a variação das variáveis estudadas. Segundo Freitas et al (2017) o alcance é uma distância dentro da qual as amostras apresentam-se correlacionadas espacialmente e sua medida é importante no planejamento e na avaliação experimental, pois pode auxiliar na definição do procedimento de amostragem. Figura 3.…”
Section: Ajustes Dos Semivariogramas Das Variáveisunclassified
See 3 more Smart Citations
“…Isto demostra que a grade amostral adotada no presente trabalho (30 x 30m) foi suficiente para expressar a variabilidade espacial das variáveis, com alcance representativo e capaz de captar a variação das variáveis estudadas. Segundo Freitas et al (2017) o alcance é uma distância dentro da qual as amostras apresentam-se correlacionadas espacialmente e sua medida é importante no planejamento e na avaliação experimental, pois pode auxiliar na definição do procedimento de amostragem. Figura 3.…”
Section: Ajustes Dos Semivariogramas Das Variáveisunclassified
“…Em função dos valores baixos do pH do solo estes resultados já seriam evidentes, pois a prática da calagem, além de corrigir a acidez também fornece Ca e Mg (Huang et al, 2021b). O cálcio atua na estabilidade da biomembrana, na construção e no fortalecimento da parede celular, além de desempenhar papel-chave no reconhecimento de patógenos invasores na membrana plasmática (Freitas et al, 2017). Em estudo realizado com laranjeiras 'Pera' (Citrus sinensis) fertilizadas com lodo de esgoto, evidenciou-se que o desbalanço nutricional entre Ca e Mg causou prejuízos à absorção de Mg (Romeiro, Grassi Filho, Moreira, 2014).…”
Section: Mapas De Krigagemunclassified
See 2 more Smart Citations
“…The yield and quality of banana were significantly improved by applying 100 kg/hm 2 of potassium fertilizer in plantations with depleted soil nutrients in Uganda. Bananas in low-potassium soils were more likely to be infected with Pseudocercospora, the pathogen that causes black Sigatoka on banana leaves [20]. It was also shown that the application of potash fertilizer, together with bio-organic fertilizers, could effectively improve the biological community structure of banana plantation soil and prevent the occurrence of Fusarium wilt [21].…”
Section: Introductionmentioning
confidence: 99%